Alterity, Values, and Socialization Human Development Within Educational Contexts (Cultural Psychology of Education,, 2018)
This book elaborates on issues regarding alterity, values, and human development in different educational contexts, serving from young children to adolescents to adults, and it claims for the need of educational contexts to consider their responsibilities regarding the development of the sociomoral dimension of human beings. The authors, experienced theorists and researchers sharing a cultural psychological perspective, provide a fresh understanding of educational institutions, and elaborate on how initiatives aiming at promoting dialogical practices and ethical orientation within educational contexts can be productive. They provide teachers, researchers, psychologists and parents, as well as the general public, with useful knowledge in order to contribute to theoretical and practical advances concerning education and human development.